RESULTS OF AN EPIGRAPHIC EXPEDITION TO THE DAHADAYEV DISTRICT OF DAGESTAN IN 2020 - Musaev, Mahac Abdulaevic; Sihaliev, Samil' Sihalievic; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2021)
Dakhadayevsky district of Dagestan is one of the most saturated with historical and cultural monuments in the republic. Among them are towers, bridges, mosques, minarets, ziyarats, cemeteries. Most of them bear inscriptions that have not been adequately studied. Meanwhile, epigraphic texts are one of the main sources of the spiritual, religious, political, social, and economic history of the region’s Middle Ages. This work presents the most remarkable examples of Arabic epigraphy, starting from the 12th century, from the villages of Amuzgi, Kubachi, Urkarakh, Kalkni, Khuduts, Ashty, and Kunki. The article gives their reading, translation into Russian, notes the features of handwriting, methods of application, draws attention to the shape of the monuments, their size, and ornamentation. Of greatest interest are texts that carry specific historical information, and dated samples, which allow, by typological similarity, to attribute the monuments of the region to a certain period of time. Among such monuments are the gravestones of 774 A.H. (1372-73), 877 x. (1472), 902 x. (1496-97), 958 x. (1551); there are historical records on stones embedded in places of worship dating back to 718 A.D. (1318-19), 765 x. (1363-64), 1035 x. (1625-26). Some of the studied inscriptions have previously been read and published, but we present our own reading. It is interesting that the inscription of 1625-26, discovered by us on the walls of the minaret, is adjacent to two texts known to science. That is, it did not come to the attention of researchers. This circumstance serves as an additional justification for the fact that when conducting epigraphic expeditions, it is necessary to cover not only territories where epigraphists have not been, but also settlements that are considered studied by scientific specialists.